Incidence of head and neck cancer among Baquba Teaching Hospital Patients - Mahdi Idan, Hayder; Shakir Motib, Anfal (Diyala Journal of Medicine, 2024)
Background: Squamous cells lining the tissues of the head and neck region, such as the nasal cavity, paranasal sinuses, oral cavity, lip, salivary glands, and hypopharynx, give growth to a group of malignancies together recognized as squamous cell carcinoma of the head and neck, which is the seventh utmost communal cancer diagnosis around the world. Objective: Determine the prevalence of head and neck cancer in Diyala province during 2022-2023 and their distribution according to age and gender of patients. In addition, this study aimed to identify the numbers of each type of head and neck cancer. Patients and Methods: A retrospective study achieved on the prevalence of head and neck cancer in the region accomplished in oncology center of Baquba teaching hospital in Diyala province, Iraq. Head and neck cancer patients recorded from 2022 to 2023. During this dated, a total of 172 patients were recorded. A search was accomplished on numerous databases, moreover, the information evaluated by age, gender and cancer type. Results: Regarding patients during 2022 (first group) which is contained of (94) patients with different head and neck cancer, 38(40.4%) were males and 56(59.6%) were females with statistically significant relationship. The patients during 2023 (second group) comprises of (78) patients with different head and neck cancer, 43(50.1%) were men and 35(44.9%) were women with statistically no significant correlation. Conclusion: Oral and pharyngeal cancer is more common in men than in women. The most common age group is 4th and 5th decade for head and neck cancer.